2020
DOI: 10.1186/s12955-020-01546-2
|View full text |Cite
|
Sign up to set email alerts
|

Measuring positive mental health and flourishing in Denmark: validation of the mental health continuum-short form (MHC-SF) and cross-cultural comparison across three countries

Abstract: Background The Mental Health Continuum–Short Form (MHC-SF) is a measure of positive mental health and flourishing, which is widely used in several countries but has not yet been validated in Denmark. This study aimed to examine its qualitative and quantitative properties in a Danish population sample and compare scores with Canada and the Netherlands. Methods Three thousand five hundred eight participants aged 16–95 filled out an electronic survey. Both the unidimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 49 publications
(43 reference statements)
5
41
0
5
Order By: Relevance
“…Taken together, our results on factor structure are well in line with the only other study, to our knowledge, that has been published thus far and included testing of the bifactor model in adolescents (Reinhardt et al, 2020). The results are also in line with recent psychometric evaluations in adults that compared other factor solutions to the bifactor model (de Bruin & du Plessis, 2015;Ferentinos et al, 2019;Hides et al, 2016;Longo et al, 2020;Luijten et al, 2019;Monteiro et al, 2020;Reinhardt et al, 2020;Rogoza et al, 2018;Santini et al, 2020). These studies and our study show that the bifactor has superior fit compared with previously tested models, including the correlated three-factor model first proposed by Keyes (C. L. Keyes, 2002, 2005Lamers et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Taken together, our results on factor structure are well in line with the only other study, to our knowledge, that has been published thus far and included testing of the bifactor model in adolescents (Reinhardt et al, 2020). The results are also in line with recent psychometric evaluations in adults that compared other factor solutions to the bifactor model (de Bruin & du Plessis, 2015;Ferentinos et al, 2019;Hides et al, 2016;Longo et al, 2020;Luijten et al, 2019;Monteiro et al, 2020;Reinhardt et al, 2020;Rogoza et al, 2018;Santini et al, 2020). These studies and our study show that the bifactor has superior fit compared with previously tested models, including the correlated three-factor model first proposed by Keyes (C. L. Keyes, 2002, 2005Lamers et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…More recently, some of these limitations were addressed by studies that tested additional methods and models (de Bruin & du Plessis, 2015;Echeverria et al, 2017;Ferentinos et al, 2019;Hides et al, 2016;Jovanovic, 2015;Longo et al, 2020;Luijten et al, 2019;Reinhardt et al, 2020;Santini et al, 2020;Żemojtel-Piotrowska et al, 2017). The bifactor model, for example, allows for evaluation of the relevance and reliability of subscale scores after controlling for the variance of the general factor (Reise, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…or languishing (i.e., low wellbeing; Keyes, 2007). Several representative population studies have shown that only a minority of the population report flourishing despite high levels of population happiness (Hone et al,2014; Huppert & So, 2013; Santini et al, 2020; Schotanus-Dijkstra et al, 2016). Combining continuous scoring of the scale and subscales with a categorical classification approach is advantageous and often used in clinical practice (Morey & Hopwood, 2019), In combination with strong psychometric properties, the MHC-SF is an attractive tool for researchers and practitioners to assess wellbeing either in isolation or conjointly with the assessment of psychological distress.…”
mentioning
confidence: 99%